1995
DOI: 10.1111/j.1399-302x.1995.tb00163.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sodium hypochlorite on potential pathogenic traits of Candida albicans and other Candida species

Abstract: Strains of Candida albicans, Candida krusei, Candida kefyr, Candida tropicalis, Candida parapsilosis and Candida guilliermondii were grown in the presence or absence of concentrations of sodium hypochlorite below the minimal inhibitory concentration and tested for a range of characteristics that may be associated with pathogenicity. Sodium hypochlorite is used routinely in hospitals in Australia for disinfection procedures, and these experiments were designed to assess the efficacy of hypochlorite as a sterili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
9

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 41 publications
(47 reference statements)
0
29
0
9
Order By: Relevance
“…However, this type of prosthesis, which is basically confectioned with thermally activated acrylic resin, constitutes a favorable environment for the colonization and proliferation of Candida genus yeasts, since these microorganisms have the ability to strongly adhere to polymethylmethacrylate, which constitutes the acrylic resin. 1,2 This phenomenon, in association with factors such as trauma, diet, poor hygiene or predisposing systemic conditions (xerostomia, hormonal alterations and immunodepression caused by diabetes mellitus or HIV infection), may lead complete denture users to develop a condition known as denture stomatitis. [3][4][5][6][7] This condition is clinically characterized by a discrete focal inflammation on the palatum, which can evolve to an intense erythema in all area covered by the denture and, in some cases, to papillary hyperplasia.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this type of prosthesis, which is basically confectioned with thermally activated acrylic resin, constitutes a favorable environment for the colonization and proliferation of Candida genus yeasts, since these microorganisms have the ability to strongly adhere to polymethylmethacrylate, which constitutes the acrylic resin. 1,2 This phenomenon, in association with factors such as trauma, diet, poor hygiene or predisposing systemic conditions (xerostomia, hormonal alterations and immunodepression caused by diabetes mellitus or HIV infection), may lead complete denture users to develop a condition known as denture stomatitis. [3][4][5][6][7] This condition is clinically characterized by a discrete focal inflammation on the palatum, which can evolve to an intense erythema in all area covered by the denture and, in some cases, to papillary hyperplasia.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 This phenomenon, in association with factors such as trauma, diet, poor hygiene or predisposing systemic conditions (xerostomia, hormonal alterations and immunodepression caused by diabetes mellitus or HIV infection), may lead complete denture users to develop a condition known as denture stomatitis. [3][4][5][6][7] This condition is clinically characterized by a discrete focal inflammation on the palatum, which can evolve to an intense erythema in all area covered by the denture and, in some cases, to papillary hyperplasia. 6 According to Daniluk et al 5 (2006), Candida genus yeasts can be isolated from the human oral cavity in 64.9% of patients with denture stomatitis, being Candida albicans the most prevalent species (78.4%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to this, Candida cells seem to have affinity with denture acrylic 23 , favoring the adhesion of epithelial cells to the oral mucosa and the onset of denture stomatitis 29 . Denture use can thus be related to the presence of Candida, which can be associated with the severity of denture-induced stomatitis, as observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…7 Some other factors, such as physiological conditions, nutritional deficiencies, 5,6 hematinics, 4 diabetes mellitus, 1,4,5,8 and the effects of chemotherapy and radiotherapy. 6 Denture-related stomatitis associated with Candida is the most common form of candidiasis, 9 which is of about 60 to 65% in a subject wearing denture. 10 The results of a study in 2007 had shown greater number of Candida (66.7-73.3%) in denture-wearer subjects of 40 to 59 years old compared with nonwearer denture subjects (39.3-34.1%).…”
Section: Introductionmentioning
confidence: 99%